Cybersecurity from a systemic perspective - Kaczmarczyk, Barbara (European Integration Studies, 2024)
Cyberspace has become a place of aggressive attacks aimed at various areas of human life. Statistics indicate a dynamic increase in cyberattacks in European Union (EU) member states and NATO countries, where technologies are developing at a rapid pace; on the one hand, this contributes to economic growth and, on the other hand, to the creation of increasingly complex cyberattack algorithms. They are aggressive and can cause significant losses. The following research methods were used to develop the article: analysis and synthesis of literature on the subject in the field of security, the state security system, cybersecurity, statistical data and legal acts. interviews were also conducted with experts in the field of security and cybersecurity systems. A systemic approach can be considered in the context of two subsystems: management and executive. The management subsystem includes the decision-making bodies of NATO and EU structures that develop a cybersecurity policy for all members of their structures, while the executive subsystem includes the armed forces and other security entities of individual EU and NATO members, as well as society on an individual (citizens) and collective (private institutions, enterprises) basis. Due to the nature of cyber threats, cyber security should be considered systemically, i.e. in a way that covers all its aspects; we should also improve cybersecurity strategies to counter threats, secure infrastructure and the green energy sector, develop technological and production resources, and enable the creation of cyber defense that is applicable both in one country and around the world.